Development of Word Writing Skills for Irregularly Spelled Consonant Rules by Using Brain-Based Learning Activity Management for Prathom Suksa 3 Students - Ninthakarn, Niranuch; Anutragulchai, Ratchaniwan (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to develop word writing skills for irregularly spelled consonant rules by using brain-based learning activity management for Prathom Suksa 3 students to have average score of more than 80% out of full score and more than 80% of total students passed the criteria, 2) to study satisfaction of students who participated brain-based learning activities. The target group consisted of Prathom Suksa 3 students at Ban Du Yai School under the Office of Khon Kaen Primary Educational Service Area 2 with the total number of 15 people. This research was pre-experimental, one-group post-test research design. The instruments used in the research were: 1) 8 plans of brain-based learning management in the standard of Thai language on irregularly spelled consonant rules and the time was taken in 8 hours. 2) Test of word writing skills for irregularly spelled consonant rules, multiple-choice type with the total number of 20 items. 3) The assessment form of students’ satisfaction on brain-based learning management with the total number of 15 items. The data were analyzed by descriptive statistics and content analysis, Statistics used in data analysis included percentage, average and standard deviation. The research results showed that : 1. Students’ word writing skills for irregularly spelled consonant rules were rated at the average score of 18.33 or 91.65% and 80% of students passed the criteria with the total number of 13 people or 86.67% which was higher than the set criteria. 2. Students’ satisfaction on brain-based learning management was rated at the highest level.